An 18-year experience of tracheoesophageal fistula and esophageal atresia - Seo, Juhee (The Korean Pediatric Society, 2010)
PURPOSE: To determine the clinical manifestations and outcomes of patients with tracheoesophageal fistula (TEF) and esophageal atresia (EA) born at a single neonatal intensive care unit. METHODS: A retrospective analysis was conducted for 97 patients with confirmed TEF and EA who were admitted to the neonatal intensive care unit between 1990 and 2007. RESULTS: The rate of prenatal diagnosis was 12%. The average gestational age and birth weight were 37(+2) weeks and 2.5±0.7 kg, respectively. Thirty-one infants were born prematurely (32%). Type C was the most common. The mean gap between the proximal and distal esophagus was 2 cm. Esophago-esophagostomy was performed in 72 patients at a mean age of 4 days after birth; gastrostomy or duodenostomy were performed in 8 patients. Forty patients exhibited vertebral, anorectal, cardiac, tracheoesophageal, renal, limb (VACTERL) association with at least 2 combined anomalies, and cardiac anomaly was the most common. The most common post-operative complications were esophageal stricture followed by gastroesophageal reflux. Balloon dilatation was performed for 1.3 times in 26 patients at a mean age of 3 months. The mortality and morbidity rates were 24% and 67%, respectively, and the most common cause of death was sepsis. The weight of approximately 40% patients was below the 10th percentile at 2 years of age. CONCLUSION: Mortality and morbidity rates of patients with TEF and EA are high as compared to those of infants with other neonatal surgical diseases. Further efforts must be taken to reduce mortality and morbidity and improve growth retardation.